Understanding designer design activity; unconscious interaction between human cognition and behaviour in everyday product / Muhammad Jameel Mohamed Kamil - Mohamed Kamil, Muhammad Jameel (Institute of Graduate Studies, UiTM, 2017)
Product designers were expected to apply their hermeneutic as well as reflective design thinking skills to find a fit between technology and human behaviour interaction, including the notion of experiencecentred. However, due to dynamics of changes in technology and the way users interact with products, the past several years have witnessed a growing interest and enthusiasm for designing the product which explicitly emphasise on user behaviour and interaction. Therefore, the recent studies have been paying attention to critically understand the elements of interaction between human and product used in everyday life. Unfortunately, it has been profound that there are limited discussions were presented within a single coherent perspective of designers’ design thinking related to the Unconscious Interaction between Human Cognition and Behaviour (UIHCB) in everyday product. In other words, a little intention has been devoted on how the UIHCB in everyday product can aid designers’ design activity. Thus, the purpose of this research is to understand designer design activity towards the UIHCB in everyday product. The research objective is to determine the attributes of unconscious interaction in everyday life, what are their responses towards the UIHCB in everyday product, how their reflective practice can be described, and how does the understanding of UIHCB in everyday product helps to aid designers’ capabilities in generating product design ideations. Four research questions have been formulated to get a firm answer posed in this research. The main empirical effort for this thesis involved qualitative and quantitative research in gathering and analysed implicit and explicit designer’s knowledge.